Effect of turbulent inflows on airfoil performance for a Horizontal Axis Wind Turbine at low Reynolds numbers (Part II: Dynamic pressure measurement). (1st October 2016) - Li, Qing'an; Kamada, Yasunari; Maeda, Takao; Murata, Junsuke; Nishida, Yusuke
Abstract: The present study aimed at highlighting the influence of turbulence on the dynamic stall characteristics of the Horizontal Axis Wind Turbine (HAWT) with wind tunnel experiments. UMY02-T01-26 airfoil that could efficiently perform at a high Reynolds number had been designed. The turbulence flow was generated by turbulence grids. To experimentally characterize these flows, HAWT blade surface pressures which were used to investigate the dynamic stall phenomenon were acquired by multiport pressure devices. The pressure distribution acting on the blade surface, lift coefficient and drag coefficient against the angle of attack were examined based on different turbulence intensities. For the angle of attack of α = 13°, the results indicated that in the increasing direction of the angle of attack, the lift coefficients of dynamic state showed larger values increase than those in the static state. At dynamic stall, in the case of Re = 1.5 × 10 5, the flow was separated at the leading edge of x/c > 0.1 in the increasing direction of the angle of attack. In the case of Re = 2.0 × 10 5, the range of the pressure hysteresis loop became narrower than that in the turbulence intensity of Re = 1.5 × 10 5 . Highlights: Surface pressures on the airfoil section were measured by multiport pressure devices. Turbulence grids were used to adjust the turbulence intensity. Dynamic stall was shown at different turbulence intensities. In the case of Re = 1.5 × 10 5, flow was separated at the leading edge of the x/c > 0.1. In the case of Re = 2.0 × 10 5, flow was delayed attachment with the increase of turbulence intensity.